Ventricular fibrillation after endoscopic retro-grade cholangiopancreatography in patient with left ventricular assist device – a case report - Georgiev, A; Pejkov, H; Kalpak, O; Bosev, M.; Janusevski, F; Jovanovski-Srceva, M; Gramatnikovski, N (Institute of Public Health of the Republic of Macedonia/Scientific Foundation SPIROSKI, 2022)
Congestive heart failure is a growing global health problem. Left ventricular assist device (LVAD) is a method used to extend the life of patients with congestive heart failure as a definitive treatment or to “bypass” the period until heart transplantation. Ventricular arrhythmias in patients with LVAD are not uncommon. The aim of this paper is to present the case of a patient with an already implanted LVAD and the need for appropriate interdisciplinary medical treatment. Case report: We present the case of a 54-year old patient, with implanted LVAD - HeartMate 3 due to severe congestive heart failure. The patient was admitted with jaundice at the PHIU Clinic for Gastroenterohepatology with performed endoscopic retrograde cholangiopancreatography (ERCP)) procedure and a stent was placed in the choledochus duct. Immeasurable blood pressure and pulse were recorded in this patient. The ECG was approaching VF (ventricular fibrillation) and it was all asymptomatic by the patient. LVAD mechanical pump leads to continuous blood flow, which means that patients with LVAD not infrequently have no pulse or measurable blood pressure. Also, in patients with LVAD, ECG pulses are with electrical disturbances. VF and ventricular tachycardia (VT) are ventricular arrhythmias that are often seen on ECG in patients with implanted LVAD. Usually these arrhythmias occur with unknown duration and terminate spontaneously. Conclusion: Patients with LVAD are prone to cardiac arrhythmias. The continuous development of medical devices leads to a continuous educational and clinical approach to patients.